Pathway Analysis for Design of Promiscuous Drugs and Selective Drug Mixtures - Sivachenko, Andrey; Kalinin, Andrey; Yuryev, Anton (Current Drug Discovery Technologies, 2006)
The decrease in the drug approval rate by the FDA and the recent failure of some blockbuster drugs has prompted a re-examination of the focus of the pharmaceutical industry on increasing drug selectivity. As a result, it has been proposed that the most efficient cure is in developing promiscuous drugs and selective drug mixtures. Rational design of drug mixtures has been nearly impossible due to the lack of information about in vivo cell regulation, mechanisms of pathway activation, and interactions between different pathways in vivo. We review the current state of the art for rational design of combination therapy and argue that the current industry-wide development of the infrastructure for pathway analysis provides unprecedented opportunity for the rational design of multicomponent and multifunctional drugs. We propose several ways how to use pathway analysis to rationally combine known drugs for either synergizing their efficacy or suppressing individual side effects.
Keywords: VEGF